Evaluation of Corneal Higher-Order Aberrations by Pentacam HR in Rural Population of Iran - Hassan Hashemi; Abbasali Yekta; Mohammadreza Aghamirsalim; Alireza Hashemi; Mehdi Khabazkhoob (Journal of Current Ophthalmology)
Purpose: To determine the distribution of corneal higher-order aberrations (HOAs) measured by pentacam HR in a rural Iranian population and their relationship with age, sex, and refractive errors. Methods: In this study, sampling was performed from villages in the north and southwest of Iran using the multistage stratified random cluster sampling method. The ocular examination included measurement of uncorrected and best-corrected visual acuity, refraction, and slit-lamp biomicroscopy. Finally, all study participants underwent corneal imaging using Pentacam HR. Results: The mean root-mean-square (RMS) (±standard error) of total HOA in the anterior and posterior corneal surfaces was 0.498 ± 0.004 μm and 0.212 ± 0.001 μm, respectively. The mean RMS of anterior and posterior spherical aberration was 0.270 ± 0.002 μm and −0.134 ± 0.001 μm, respectively. The mean RMS of anterior horizontal and vertical coma was −0.084 ± 0.003 μm and 0.029 ± 0.004 μm, respectively. The mean RMS of posterior horizontal and vertical coma was 0.011 ± 0.001 μm and −0.011 ± 0.001 μm, respectively. The anterior HOAs were significantly different between age, sex, and refractive groups (all P < 0.05). The total anterior HOA had a statistically significant relationship with the male sex, older age, higher mean keratometry (K), and hyperopia. The anterior spherical aberration was significantly directly related to age, mean K, and hyperopia and inversely related to myopia. Conclusions: The amounts of HOAs in the present study were different from previous studies, and these residence place differences (urban/rural) in the HOAs should be taken into account when designing refractive surgery nomograms and therapeutic and diagnostic considerations in each population. Moreover, the corneal HOAs, especially on the anterior surface, increased significantly with aging.